2018
DOI: 10.26623/themessenger.v10i2.782
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of News Construction and Netizen Response to the Hoax News in Online Media

Abstract: <p><em><span class="tlid-translation"><em><span>This study aims to determine the effect of news in online media on the thoughts and behavior of a person, because the impact is very strong in shaping public opinion. This study uses theory of mass communication, news construction, netizen response, online media. The research method used quantitative descriptive analysis with online data collection techniques. Conclusion of research (1) News construction have positive effect to repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
1
Order By: Relevance
“…The study about journalist professional versus employeecase of Koran Sindo in Censoring News on Trump' Travel Ban Policy was conducted by Tjipta Lesmana. Another research was held by Dendy Suseno about Influence of News Construction and netizen response to hoax news on the online media (Adhiarso, Utari, & Hastjarjo, 2018). Research about news authorship and news sources was conducted by Ogadimma (Emenyeonu & Mohamad, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The study about journalist professional versus employeecase of Koran Sindo in Censoring News on Trump' Travel Ban Policy was conducted by Tjipta Lesmana. Another research was held by Dendy Suseno about Influence of News Construction and netizen response to hoax news on the online media (Adhiarso, Utari, & Hastjarjo, 2018). Research about news authorship and news sources was conducted by Ogadimma (Emenyeonu & Mohamad, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Another example, based on the confession of a journalist in a newspaper in Semarang who did not want to be named said that the intervention of the media from the internal editorial causes the issuance of an information becoming not objective (Pratono, 2014). Politics of newsroom is also influenced by the fact that the media is actually not a sterile space from various interests (Adhiarso et al, 2018). The reality of the media is not always the same and congruent with public reality, because the news can be constructed by various interests, both from outside the media and within the media itself (Machmud, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Response" shown that the more netizens arise, the more deceitful news will be broader and more liars without reference to journalism (Adhiarso et al, 2018). With the dataset of 750 user comments from guardian online, the daily telegraph online, and times online, (Neurauter-Kessels, 2011) That is the advantage of online media, interactivity.…”
Section: Study Of "Hoax News In Online Media Reviewed From News Const...mentioning
confidence: 99%